Late Proterozoic stratigraphy, U–Pb zircon ages, and rift tectonics, Mackenzie Mountains, northwestern Canada - Jefferson, C. W.; Parrish, R. R. (Canadian Journal of Earth Sciences, 1989)
Stratigraphic evidence suggests sporadic rifting began during deposition of the mainly platformal Mackenzie Mountains Supergroup: minor magnetite iron-formation in shale basins, lead–zinc in karsted and brecciated carbonates, red-bed and evaporite wedges, and basalts at the top. In the unconformably overlying Coates Lake Group similar climates and definite rifting are recorded by thin orthoconglomerates with thick red-bed and evaporite wedges containing stratiform copper deposits in paleovalleys. Unconformably above this, basal Windermere Supergroup records major climatic change and more emphatic rifting, with thick orthoconglomerates next to fault scarps overlain by glaciomarine deposits with volcanics and hydrothermal iron-formation.A quartz diorite plug, here dated by the U–Pb zircon method at [Formula: see text], is bounded by faults but is contained in a thrust panel together with Mackenzie Mountains Supergroup and is chemically similar to diabase sills previously dated at 766–769 ± 27 Ma (Rb–Sr). A diatreme intruding Coates Lake Group contains clasts of granite and gneiss from inferred basement. U–Pb systematics from a granite clast indicate inherited zircons about 1.6 ± 0.25 Ga in age and crystallization between 1100 and 1175 Ma, a maximum age for Mackenzie Mountains Supergroup.